Quantitative Analysis of Milk-Derived microRNAs and Microbiota during the Manufacturing and Ripening of Soft Cheese - Oh, Sangnam; Park, Mi-Ri; Ryu, Sangdon; Maburutse, Brighton E.; Kim, Ji-Uk; Kim, Younghoon (Journal of microbiology and biotechnology, 2017)
MicroRNAs (miRNAs) are abundant in bovine milk and milk derived from other livestock, and they have functional roles in infants and in the secretion process of mammary glands. However, few studies have evaluated miRNAs in dairy processes, such as during cheese making and ripening. Thus, we investigated the characteristics of milk-derived miRNAs during the manufacturing and ripening of Camembert cheese as well as the microbiota present using the quantitative reverse transcription polymer chain reaction (RT-qPCR) and 16S rRNA pyrosequencing, respectively. Pyrosequencing showed that the cheese microbiota changed dramatically during cheese processing, including during the pasteurization, starter culture, and ripening stages. Our results indicated that the RNA contents per 200 mg/200 μl of the sample increased significantly during cheese-making and ripening. The inner cheese fractions had higher RNA contents than the surfaces after 12 and 22 days of ripening in a timedependent manner (21.9 and 13.2 times higher in the inner and surface fractions than raw milk, respectively). We performed a comparative analysis of the miRNAs in each fraction by RT-qPCR. Large amounts of miRNAs ( , and ) correlated with immune responses and mammary glands were present in aged cheese, with the exception of , which was not present on the surface. Considerable amounts of miRNAs were also detected in whey, which is usually disposed of during the cheese-making process. Unexpectedly, there were no significant correlations between immune-related miRNAs and the microbial populations during cheese processing. Taken together, these results show that various functional miRNAs are present in cheese during its manufacture and that they are dramatically increased in amount in ripened Camembert cheese, with differences according to depth.